Expansion of NATO. - Neal, Bobby E. (2009)
The North Atlantic Treaty Organization (NATO) was formed in 1949 and is one of the most successful military alliances in history; its headquarters is in Brussels. The main purpose for forming NATO was to prevent an attack by the Soviet Union on the non-communist nations of Western Europe (Jackson, 1999). NATO originally alliance consisted of 12 members: the United States, Britain, France, Canada, Italy, the Netherlands, Belgium, Luxembourg, Denmark, Iceland, Norway, and Portugal. In the year of 1952, Greece, and Turkey joined the alliance; there are a total of 26 members today. NATO has been very instrumental in keeping peace and order among countries in the West. The expansion of NATO to new members would prompt constraints in resources and end the legacy as being the greatest organization ever created today.